Possibility of alleviating dextran sulfate sodium-induced colitis in mice by modulate intestinal barrier function and gut microbiota with laminarin acetyl esters - Kit-Leong Cheong; Amanullah Sabir; Suresh Veeraperumal; Franck Quero; Rui Li; Qiaoli Zhao; Karsoon Tan; Saiyi Zhong; Udayakumar Veerabagu (Carbohydrate Polymer Technologies and Applications)
This study investigates the esterification of laminarin, a β-glucan polysaccharide, using trifluoroacetic anhydride and acetic acid to synthesize laminarin acetyl esters (LA) with potential therapeutic properties. The efficacy of LA was evaluated in an in vivo dextran sulfate sodium induced colitis mouse model. Treatment with LA significantly improved the organ index and modulated inflammatory responses by upregulating anti-inflammatory cytokines, such as IL-10 and TGF-β1. LA also promoted a favorable shift in gut microbiota composition, notably increasing the relative abundance of beneficial bacteria like Lactobacillus and Bifidobacterium, and enhancing short-chain fatty acid production, particularly acetic acid. Immunohistochemical analysis revealed a reduction in CD68 expression and an elevation in CD163 expression, indicating a shift toward an anti-inflammatory macrophage phenotype. These findings demonstrate that LA mitigates pro-inflammatory responses, enhances gut barrier integrity, and supports a healthy gut microbiota, underscoring its potential as a therapeutic agent for managing colitis and improving gut health.